Shaping Honest Citizens: Reframing Anti-Corruption Education in Primary Schools for a Culture of Integrity - Muh. Asharif Suleman; Zulfi Idayanti; M. Hulkin; Amalia Alfina Siagian; Khairina Habib Rangkuti; Nindya Putri (Yayasan Zia Salsabila, 2025)
Corruption remains deeply entrenched across various sectors of society, underscoring the urgent need for systematic and sustainable countermeasures. One promising approach is the early integration of anti-corruption education at the primary school level to foster a culture of integrity from a young age. This study employs a qualitative approach through a comprehensive literature review of scholarly articles, policy documents, and relevant educational frameworks. The analysis by meta-analysis, focuses on three key dimensions: (1) the conceptual foundation of anti-corruption education, (2) its significance in the context of primary education, and (3) the core values that underpin anti-corruption learning. The study highlights the strategic role of anti-corruption education in shaping students’ character and moral reasoning. Findings emphasize the necessity of embedding anti-corruption values into formal curricula and underscore the pivotal role of teachers as primary agents of value transmission and ethical modeling in the classroom. This study contributes to the discourse on value-based education and offers recommendations for embedding anti-corruption education as an integral component of character development in early education.